17. Knowledge of Understanding the Relationship of Sexual desire’s Symptoms of Lust with the Success of Artificial Insemination on Cattle Farmer at the Lengayang subdistrict, Pesisir Selatan district, West Sumatera - Nida Ulfa Dilla; Cut Nila Thasmi; Hamdan Hamdan (Universitas Syiah Kuala, 2017)
This study aimed to find out the understanding of cattle farmer in Lengayang, Pesisir Selatan West Sumatera about the relation of sexual desire symptom with the success rate of artificial insemination on cattle. The respondents of this study were the cattle farmer on Lengayang base on the result of the method of this study was field survey. The data were collected interview the farmer using structural questioner form. The data consist of secondary and primary data. The secondary data were obtained from Animal Husbandry departement and Animal Health on Pesisir Selatan. Data were analyzed descriptively. Result showed that from 100 respondents there were 15 respondents from Lakitan village, 16 respondent from East Lakitan, 14 respondents from East Kambang, 35 respondents from West Kambang, 9 respondents from Kambang and 11 respondents from North Kambang. Based on the study result the level of farmers knowledge about understanding relation sexual desire the symptoms with the success of artificial insemination in cattle is 2% excellent, 33% good, 56% fairly good and 9%. Less Good. Based on Regression test formal education, non-formal education and experience effect of to the knowledge of the success of artificial insemination 6.6%